1987
DOI: 10.1038/eye.1987.78
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of quinine blindness

Abstract: SummaryAn experimental model of qumme induced blindness is presented. Elec trophysiological, angiographical and morphological examinations were made. The occurrence of blindness and any recovery from blindness was dependent upon the dose of quinine taken. As no evidence of acute retinal ischaemia was found it is concluded that quinine is retinotoxic.Despite the many clinicaP and experimentaF reports of quinine blindness providing much detailed evidence and analysis, the first line of clinical therapy continues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…[12][13][14][15] Elapsed time from most recently administered quinine infusion (QET) was measured. A significant positive association was found between QET and both maximal-response a wave amplitude (P ¼ 0.03) and cone a wave amplitude (P ¼ 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Elapsed time from most recently administered quinine infusion (QET) was measured. A significant positive association was found between QET and both maximal-response a wave amplitude (P ¼ 0.03) and cone a wave amplitude (P ¼ 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…This product has yet to be defined (to our knowledge) and may be released in small concen¬ trations but must be capable of induc¬ ing strong "hormonelike" effects when bound to the appropriate recep¬ tor. 11 The second theory relates to the possibility of autoimmune reactions triggered by the host's response to tumor antigens that cross-react with specific retinal components. Several investigators have reported the pro¬ duction of antiretina immunoglobu¬ lins in patients with cancer1416 and demonstrated immune reactions by the serum samples of patients with CAR to in vitro cultivated lung cancer cells.…”
mentioning
confidence: 99%
“…The exact mechanism by which CQ and HCQ cause retinal toxicity is yet to be determined. Data from in‐vitro and animal model studies suggest that the drugs accumulate in RPE cells, inhibit the recycling of all‐trans‐retinol and might result in photoreceptor degeneration 3,29 . However, recent data from SD‐OCT scans in humans suggest an alternative sequence of events in which the primary site of toxicity is the photoreceptor layer, with secondary effect on RPE cells 30 …”
Section: Discussionmentioning
confidence: 99%